2003
DOI: 10.1002/cncr.11442
|View full text |Cite
|
Sign up to set email alerts
|

Papillary microcarcinoma of the thyroid—Prognostic significance of lymph node metastasis and multifocality

Abstract: Portable electronic devices operate at varying power demand levels. This variability of power demand must be considered explicitly in the design of man‐portable power generation systems for acceptable performance and portability. In this regard, a mathematical programming based design method is proposed. The method transcribes optimal operation of the system at a given power demand into a mathematical program. The power demand specific programs are incorporated into another upper level mathematical program enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
481
16
39

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 678 publications
(571 citation statements)
references
References 40 publications
35
481
16
39
Order By: Relevance
“…Someone think that CLND is unnecessary, because the reported mortality rates of PTMC range from 0% to 1%, and CLND provides no survival benefit (Appetecchia et al, 2002), CLND may increase the frequency of perioperative complications as well (Wada et al, 2003). However, other studies demonstrated that the risk of recurrence significantly increased in PTMC patients with CLNM (Chow et al, 2003). In addition, some investigators have showed that the operations for recurred lymph nodes in PTC increased the risk of postoperative complications (Vini et al, 2003) .…”
Section: Discussionmentioning
confidence: 99%
“…Someone think that CLND is unnecessary, because the reported mortality rates of PTMC range from 0% to 1%, and CLND provides no survival benefit (Appetecchia et al, 2002), CLND may increase the frequency of perioperative complications as well (Wada et al, 2003). However, other studies demonstrated that the risk of recurrence significantly increased in PTMC patients with CLNM (Chow et al, 2003). In addition, some investigators have showed that the operations for recurred lymph nodes in PTC increased the risk of postoperative complications (Vini et al, 2003) .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, however, the prevalence of clinical thyroid papillary carcinoma was 1.9-11.7 per 100,000 females of all ages [3,10], which is about 1,000 times lower than that of PMC detected on ultrasonography. The marked difference between these prevalences suggests that PMC rarely grow and become clinically apparent, prompting the question of whether immediate surgery is mandatory for all PMC detected on mass screening, although PMC is also known to show multicentricity in 15-44% of lesions and regional lymph node metastasis in 14-64% of lesions [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…8 Although its clinical significance in papillary microcarcinomas is somewhat controversial, several authors have reported that lymph node metastasis at presentation is correlated with loco-regional recurrence in papillary microcarcinomas. 5,[9][10][11] Moreover, lymph node metastasis is reported to be associated with distant metastasis of papillary microcarcinomas. [9][10][11] In the new TNM (tumor, node, metastases) staging system, lymph node metastasis is a more important factor than tumor size in overall staging.…”
mentioning
confidence: 99%
“…5,[9][10][11] Moreover, lymph node metastasis is reported to be associated with distant metastasis of papillary microcarcinomas. [9][10][11] In the new TNM (tumor, node, metastases) staging system, lymph node metastasis is a more important factor than tumor size in overall staging. 12 Overexpression of cyclin D1, 13 S100A4 14 and MUC1, 15 loss of p27 13,16 and presence of the BRAF mutation 17,18 have been suggested as important predictive factors for relapse or nodal metastasis of papillary thyroid carcinoma.…”
mentioning
confidence: 99%